PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN, RELIGIUSITAS, DAN KEPERCAYAAN TERHADAP MINAT PENGGUNAAN MOBILE BANKING BANK SYARIAH PADA MASYARAKAT PEDESAAN KABUPATEN SIDOARJO - Andini, Annisa Putri; Indrarini, Rachma (Universitas Negeri Surabaya, 2024)
Technological developments have entered the Islamic financial industry, causing transaction activities that can be carried out online, one of which is through Mobile Banking at Islamic Banks. This study aims to examine the Perceived ease of use, Religiosity, and Trust in the interset in using Islamic Bank Mobile Banking at Sidoarjo community. The study used a quantitative method with an assosiative approach. The data used in this reseacrh were obtained from questionnaire with total total of 170 respondents from sampling using purposive sampling. The data analyzed using Structural Equation Modelling-Partial Least Square (SEM-PLS). The results in this study state that the perceived ease of use does not have a significant effect on the interest in using Islamic Bank Mobile Banking because the public already understands that using mobile banking can provide convenience in all transactions so whether the mobile banking system is easy or not does not affect the public to use mobile banking, religiosity has a significant positive effect on the interest in using Islamic Bank Mobile Banking so that religiosity affects the actions of the public to use or use a product including the use of services from Islamic banking, namely mobile banking, and trust in Mobile Banking has a significant positive effect on the interest in using Islamic Bank Mobile Banking because the public understands that the use of mobile banking is based on a sense of trust that the service is reliable.